Supporting health equity for First Nations, Inuit and Métis peoples - Margo Greenwood; Donna Atkinson; Julie Sutherland (Canada Communicable Disease Report, 2022)
The National Collaborating Centre for Indigenous Health (NCCIH) is unique among the National Collaborating Centres as the only centre focused on the health of a population. In this fifth article of the Canada Communicable Disease Report’s series on the National Collaborating Centres and their contribution to Canada’s public health response to the coronavirus disease 2019 (COVID-19) pandemic, we describe the work of the NCCIH. We begin with a brief overview of the NCCIH’s mandate and priority areas, describing how it works, who it serves and how it has remained flexible and responsive to evolving Indigenous public health needs. Key knowledge translation and exchange activities undertaken by the NCCIH to address COVID-19 misinformation and to support the timely use of Indigenous-informed evidence and knowledge in public health decision-making during the pandemic are also discussed, with a focus on acting on lessons learned moving forward.